GABA and astrocytic cholesterol determine the lipid environment of GABAAR in cultured cortical neurons - Zixuan Yuan; Mahmud Arif Pavel; Scott B. Hansen (Communications Biology)
Abstract The γ-aminobutyric acid (GABA) type A receptor (GABAAR), a GABA activated pentameric chloride channel, mediates fast inhibitory neurotransmission in the brain. The lipid environment is critical for GABAAR function. How lipids regulate the channel in the cell membrane is not fully understood. Here we employed super resolution imaging of lipids to demonstrate that the agonist GABA induces a rapid and reversible membrane translocation of GABAAR to phosphatidylinositol 4,5-bisphosphate (PIP2) clusters in mouse primary cortical neurons. This translocation relies on nanoscopic separation of PIP2 clusters and lipid rafts (cholesterol-dependent ganglioside clusters). In a resting state, the GABAAR associates with lipid rafts and this colocalization is enhanced by uptake of astrocytic secretions. These astrocytic secretions delay desensitization and enhance maximum current. In an Alzheimer’s Disease (AD) mouse model with high brain cholesterol, GABAAR shifts into lipid rafts. Our findings suggest cholesterol is a signaling molecule and astrocytes regulates GABAARs in neurons by secreting cholesterol. The findings have implications for treating mood disorders and AD associated with altered brain lipids.